2019
DOI: 10.1016/j.fishres.2019.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Influences of angler subsidies on the trophic ecology of European barbel Barbus barbus

Abstract: European barbel Barbus barbus is a recreationally important riverine fish that is widely introduced outside of its natural range. Contemporary angling practices for B. barbus involve the use of baits based on marine fishmeal (MF). MF is isotopically distinct from freshwater prey via highly enriched δ 13 C and thus its dietary influence on B. barbus can be tested via differences in fractionation factors (Δ 13 C). Correspondingly, stable isotope data from 11 riverine B. barbus populations tested how their trophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…For example, Mehner et al (2019) revealed that after a 3-month exposure period to these baits in a German lake, some omnivorous cyprinid species had diets comprising substantial amounts of these baits. Adult European barbel in 11 English rivers all showed patterns of strong δ 13 C enrichment away from macroinvertebrate putative prey resources, with this enrichment associated with the high consumption of marine fishmeal baits (De Santis et al, 2019), with this also apparent in adult chub Squalius cephalus (Gutmann Roberts & Britton, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mehner et al (2019) revealed that after a 3-month exposure period to these baits in a German lake, some omnivorous cyprinid species had diets comprising substantial amounts of these baits. Adult European barbel in 11 English rivers all showed patterns of strong δ 13 C enrichment away from macroinvertebrate putative prey resources, with this enrichment associated with the high consumption of marine fishmeal baits (De Santis et al, 2019), with this also apparent in adult chub Squalius cephalus (Gutmann Roberts & Britton, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Corn and boilie baits are also strongly δ 13 C enriched versus natural prey resources, with these differences enabling their diet contributions to be quantified after a 3‐month exposure period in the cyprinid fishes (high contribution in some species) and macroinvertebrates (low contribution) of a German lake (Mehner et al, 2019). This isotopic differentiation between natural prey and angler baits means that when fish feed on these baits, it would be expected that their isotopic niche (analogous to the trophic niche; Jackson et al, 2012) would shift to enriched δ 13 C (Bašić et al, 2015; De Santis et al, 2019). The extent of this δ 13 C enrichment would be dependent upon the proportion of angling baits in their diet, with higher proportions resulting in greater shifts (Gutmann Roberts et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high proportion of prey fishes in the diet of the introgressed barbel of TL i aligns to some B. barbus populations having diets in which prey fishes are present, albeit usually in low frequencies (Piria et al 2005 ; Gutmann Roberts et al 2017 ). Recreational anglers also frequently capture larger individuals on baits comprising of high proportions of marine fishmeal, suggesting that fish prey are attractive to adult B. barbus (De Santis et al 2019 ). The barbel of TL i were the only population here where small benthic fishes were detected at relatively high frequency in diet by GCA, despite considerable overlap in the body sizes present, and the presence of small benthic fishes in all sites.…”
Section: Discussionmentioning
confidence: 99%
“…In rivers in eastern England, they coexist as native species, as barbel is considered indigenous in these areas due to its post‐Pleistocene colonisation of eastern flowing rivers that had connection with the Rhine and Danube (Antognazza et al., 2016; Wheeler & Jordan, 1990). The relatively large body sizes and omnivory of both species suggest they will also share similar prey resources, especially in the absence of recreational angling that can otherwise result in some barbel feeding mainly on angler bait (De Santis et al., 2019). Correspondingly, using a pond mesocosm experiment with chub as the model species and barbel as the co‐existing released species, the experiment tested the relative strength of increased inter‐ and intra‐specific competition on chub somatic growth rates, and their trophic and isotopic niche sizes.…”
Section: Introductionmentioning
confidence: 99%